Steps in tooth treatment with fiberglass post: a literature review (Research, Society and Development, 2021)
Introduction: The fiberglass post is a retaining material used to support restorations or prostheses, which does not cause stress or fracture to the tooth structure. Its benefits range from mechanical properties similar to dental tissue, to good aesthetic results and longevity. Thus, it is a good option for replacing the cast metal post, mainly due to its adhesive characteristic to resin cement, in addition to having a simple and fast clinical execution. Objective: To analyze, through a narrative literature review, the structure and function of the fiberglass post and explore its attributes. Methodology: This is a literature review, in which searches were performed in worldwide bibliographic databases such as: Pubmed, Scielo, Academic Google, Lilacs and Cocrhane. Articles and works published between 2010 and 2021, written in English, Portuguese and Spanish were selected. Results: Anatomic posts coated with composite resin resulted in the highest fracture resistance compared to other methods. Closure: The fiberglass post is commonly used in dentistry with the main objective of affixing the coronary restoration, repairing, in this way, function and shape to the dental element. The use of the intraradicular retainer has been progressively spread, as it is a material with good aesthetic and mechanical characteristics, ideal for remaining teeth, in addition to having biocompatibility.